A Concise and Practical Semisynthesis of Ecteinascidin 743 and (–)‐Jorumycin. Issue 5 (6th February 2017) - Xu, Shanghu; Wang, Guan; Zhu, Jinjin; Shen, Chuang; Yang, Zhezhou; Yu, Jun; Li, Zhong; Lin, Tanghuan; Sun, Xun; Zhang, Fuli
Abstract : Ecteinascidin 743 is an antitumor drug used to treat specific soft‐tissue sarcomas (STS). In this paper, we present a concise and practical semisynthesis of ecteinascidin 743 starting from safracin B. The strategy involves the direct conversion of an aliphatic amino group into an acetoxy group. By this approach, ecteinascidin 743 was synthesized in 14 steps and 1.5 % overall yield. The synthetic approach also provided access to other tetrahydroisoquinoline alkaloids, such as (–)‐jorumycin (a promising anticancer candidate). (–)‐Jorumycin was prepared in six steps and 24.1 % overall yield from safracin B. Abstract : Ecteinascidin 743 (an anticancer drug) was synthesized from safracin B in 14 steps in 1.5 % overall yield. The strategy involves the direct conversion of an aliphatic amino group into an acetoxy group. This synthetic approach was also used to synthesize (–)‐jorumycin (a promising anticancer candidate). (–)‐Jorumycin was prepared in six steps from safracin B in 24.1 % overall yield.